Surface texturing of si with periodically arrayed oblique nanopillars to achieve antireflection - Kim, Jun Hyun; You, Sanghyun; Kim, Chang Koo (Materials, 2021)
Si surfaces were texturized with periodically arrayed oblique nanopillars using slanted plasma etching, and their optical reflectance was measured. The weighted mean reflectance (Rw) of the nanopillar-arrayed Si substrate decreased monotonically with increasing angles of the nanopillars. This may have resulted from the increase in the aspect ratio of the trenches between the nanopillars at oblique angles due to the shadowing effect. When the aspect ratios of the trenches between the nanopillars at 0◦ (vertical) and 40◦ (oblique) were equal, the Rw of the Si substrates arrayed with nanopillars at 40◦ was lower than that at 0◦ . This study suggests that surface texturing of Si with oblique nanopillars reduces light reflection compared to using a conventional array of vertical nanopillars.
Keywords: Anti-reflection; Oblique angles; Optical reflectance; Shadowing effects; Si substrates; Si surfaces; Surface-texturing; Weighted mean; Antireflection; Light reflection; Oblique nanopillars; Slanted plasma etching; Surface texturing